The horn of plenty de McQueen: uma conjunção paródica entre o design, a moda e a arte no contemporâneo - Camargo, Andréa Barbosa [UNESP] (2015)
Our goal is to understand how McQueen uses art, spectacle, as anti-establishment activation scenario before the contemporary world events. To this end, we will examine five looks from the collection the horn of plenty, 2009. This collection has a conceptual character that identifies with art. In fashion desing conceptual term refers artistic and faciful side of the designer, in which he can sketch contrasting ideas with the usual seen in the market, but that connote styles that will be part of its commercial collection (the one sold to the consumer market). It isthe conceptual design that the designer is know in the media because it represents the apotheosis of their work; is the shaw where the creator shows all his talent waiting for approval from the audience. However, in addition to adversiting character, the current show has a contester characteristic, idealistic, to be recognized in this research as a powerful communication channel. Where we may ask: How contemporary is revealed critically the work of McQueen, the horn of plenty? We use as theoretical framework to answer these questions, the theory of transtextuality that emerged from the Intertextuality of Kristeva, this underpinned by the notion of dialogism Bakhtin. The transtextuality was proposed by Gerard Genette from the broader concept of Intertextuality. This theory concerns the definition of a set of texts and the relationships established between them and also constitutes the reworking of textual past. Thus we see parodic bios McQueen's work that linked to many intertexts generated characters with critical and ironic charge, while permeated with artistic expression